2021
DOI: 10.3390/su13063580
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Green User Entrepreneurs’ Performance—Is Sustainability an Asset or a Liability for Innovators?

Abstract: User entrepreneurs rely on regular consumers when starting their business, for example, when raising creative and financial support. This research examines regular consumers’ opinions with regard to the future business performance of green vs. non-green user entrepreneurs. We build on previous consumer behavior research on consumers’ performance perceptions. Specifically, consumers perceive products that use green, environmentally friendly technologies as having inferior performance compared to products that u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Another branch of the literature stated the obvious influence of consumers, competitors, and governments on corporations' decision-making in the perspective of stakeholder's theory [27,102,103]. Möller and Herm [104] explored the evaluated performance of green entrepreneurs through investigating a group of consumers, and they found consumers with high environmental values would make higher grades on entrepreneurs than the consumers with low environmental values. It indirectly revealed that the pressure from consumers would make a difference.…”
Section: External Environment Perception and Corporate Behaviormentioning
confidence: 99%
“…Another branch of the literature stated the obvious influence of consumers, competitors, and governments on corporations' decision-making in the perspective of stakeholder's theory [27,102,103]. Möller and Herm [104] explored the evaluated performance of green entrepreneurs through investigating a group of consumers, and they found consumers with high environmental values would make higher grades on entrepreneurs than the consumers with low environmental values. It indirectly revealed that the pressure from consumers would make a difference.…”
Section: External Environment Perception and Corporate Behaviormentioning
confidence: 99%
“…Users or organizations with green consumption behavior can usually show greater advantages in competition (Banytė et al, 2020). Möller and Herm (2021) investigated consumers' views on green and non-green user entrepreneurs. The results show that consumers who identify with green user entrepreneurs have strong green values.…”
Section: Green Users and Green Consumer Behaviormentioning
confidence: 99%
“…The qualitative study focused on insidersbusiness owners, directors, managers, and researchers-to identify their motivations, personal beliefs, and actions or behaviors toward (sustainable) transitional effects. Möller and Herm [37] defined user innovators as consumers who contemplate starting a company and bringing innovation to the market. User innovators are classified as green entrepreneurs when they profess environmentalism.…”
Section: Synthesis Of Current Special Issue Contributionsmentioning
confidence: 99%